Knowledge of Chinese dentists on HPV, their willingness and barriers to recommend HPV vaccination to patients - Haoyue Xu; Kai Song; Lizheng Qin; Yi Qu; Qifang Niu; Bo Li; Zhengxue Han (Human Vaccines & Immunotherapeutics, 2021)
Objective: This study aimed to assess the knowledge of Chinese dentists on human papilloma virus (HPV), their willingness and factors prevention them from recommending patients for HPV vaccination, and to identify ways through which dentists can acquire HPV-related knowledge. Methods: This was a cross-sectional study based on Chinese dentists. The anonymous self-filled questionnaire method was used to collect demographic information of participants, their knowledge of HPV, willingness and barriers to recommending HPV vaccines to patients, and the strategies they can adopt to obtain HPV-related knowledge. Results: A total of 517 dentists completed the questionnaire, and 89.94% of dentists were willing to recommend HPV vaccination to patients. Participants aged 30–39 years, male dentists and dentist-in-charge had relatively lower knowledge scores than other groups. Besides, participants aged 30–39 years, working in private hospitals, and practicing in Southern China had a lower willingness to recommend HPV vaccination to patients. Recommending HPV vaccination to patients is not within the scope of practicing dentists, and concerns about the safety of the HPV vaccine were found to be the main barriers preventing its recommendation. Notably, 97.87% of dentists were eager to acquire HPV-related knowledge, and agreed for the first time to enroll in relevant educational courses. Conclusion: Chinese dentists had expressed a strong desire to recommend HPV vaccines to patients, even though their knowledge of HPV was scanty. Therefore, measures to improve their understanding of HPV vaccines and eliminate barriers suppressing their willingness to recommend HPV vaccines are urgently needed.